Faktor-Faktor Yang Berhubungan Dengan Depresi Pada Pasien Diabetes Mellitus Tipe-2 Di Grha Diabetika Surakarta - Sari, Intan NUr Indah, Anisa Catur Wijayanti, SKM., M.Epid, s (2016)
Depression is an illness caused by the impact of Diabetes Mellitus. As a result of a shift in lifestyle then DM experienced earlier and longer causes sufferers to experience diabetes during their lifetime. There are several factors that cause depression in patients with Type-II diabetes. The research objective was to determine the factors associated with depression in patients with Type-II diabetes in diabetic GRHA Surakarta. The study design was observational quantitative research with cross-sectional design. Data were collected through interviews include characteristics of respondents, knowledge, long- suffering, and family support with a sample of 137 respondents. The results showed that the knowledge factor significantly associated with depressive patients with DM (p= 0.013), whereas long-suffering (p = 0.594) and family support (p = 0.591) was not significantly associated with depressive patients with DM. Depression is very likely prevented in diabetic patients when all lines taking part in self-care in patients.